2015
DOI: 10.1097/sap.0000000000000342
|View full text |Cite
|
Sign up to set email alerts
|

Skin-Derived Precursor Cells Promote Wound Healing in Diabetic Mice

Abstract: Skin-derived precursor cells promoted diabetic wound healings through vasculogenesis at the early stage of wound healing. Skin-derived precursor cells are a possible therapeutic tool for diabetic impaired wound healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 33 publications
1
19
0
1
Order By: Relevance
“…Model animals frequently used in pre-clinical studies of wound healing are rats and mice. Transgenic mouse models have contributed to the field in terms of specific gene products and their contribution to the wound healing process (185, 186) and by providing disease models (187,188). The translational problem that stems from using rodents is that the biology of the skin and subsequently the wound healing process in rodents is different from human.…”
Section: Modelling Skin and Wound Healingmentioning
confidence: 99%
“…Model animals frequently used in pre-clinical studies of wound healing are rats and mice. Transgenic mouse models have contributed to the field in terms of specific gene products and their contribution to the wound healing process (185, 186) and by providing disease models (187,188). The translational problem that stems from using rodents is that the biology of the skin and subsequently the wound healing process in rodents is different from human.…”
Section: Modelling Skin and Wound Healingmentioning
confidence: 99%
“…It was also found that transplanted SKPs differentiated into peripheral nerve fibres within the wounds by D28. The authors of the study concluded that wound healing was improved as a result of increased neovascularisation promoted by SKPs (Sato et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that populations of hair follicle stem cells residing in the bulge, isthmus and infundibulum are able to contribute to wound repair in both the short-and long-term (Ito et al, 2005a;Levy et al, 2007;Plikus et al, 2012). Recent studies have also shown that cells derived from the DP may improve skin wound healing (Sato et al, 2015). In addition, wound re-epithelialisation has been shown to be improved when surrounding hair follicles are in anagen, with a correlation described between the genes upregulated during anagen and those that improve wound healing (Ansell et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations